Deltamethrin resistance in Aedes aegypti results in treatment failure in Merida, Mexico. - Gonzalo M Vazquez-Prokopec; Anuar Medina-Barreiro; Azael Che-Mendoza; Felipe Dzul-Manzanilla; Fabian Correa-Morales; Guillermo Guillermo-May; Wilbert Bibiano-Marín; Valentín Uc-Puc; Eduardo Geded-Moreno; José Vadillo-Sánchez; Jorge Palacio-Vargas; Scott A Ritchie; et al. (Public Library of Science (PLoS), 2017)
The operational impact of deltamethrin resistance on the efficacy of indoor insecticide applications to control Aedes aegypti was evaluated in Merida, Mexico. A randomized controlled trial quantified the efficacy of indoor residual spraying (IRS) against adult Ae. aegypti in houses treated with either deltamethrin (to which local Ae. aegypti expressed a high degree of resistance) or bendiocarb (to which local Ae. aegypti were fully susceptible) as compared to untreated control houses. All adult Ae. aegypti infestation indices during 3 months post-spraying were significantly lower in houses treated with bendiocarb compared to untreated houses (odds ratio <0.75; incidence rate ratio < 0.65) whereas no statistically significant difference was detected between the untreated and the deltamethrin-treated houses. On average, bendiocarb spraying reduced Ae. aegypti abundance by 60% during a 3-month period. Results demonstrate that vector control efficacy can be significantly compromised when the insecticide resistance status of Ae. aegypti populations is not taken into consideration.